The influence of institutional ownership, independent commissioners, and capital intensity on tax avoidance: Evidence from LQ45 non-bank companies in Indonesia - Aulia, Aliza Rachma; Irawan, Ferry (Educoretax, 2025)
This study examines how institutional ownership, independent commissioners, and capital intensity influence tax avoidance in non-bank LQ45 index companies in Indonesia during 2019-2022. Using a quantitative approach with secondary data from 42 companies (168 firm-year observations), we employed panel data regression with Book Tax Difference as the tax avoidance proxy. Results show that institutional ownership and independent commissioners have no significant impact on tax avoidance, while capital intensity positively influences tax avoidance practices. This suggests that companies with higher fixed asset proportions engage more in tax avoidance, likely through depreciation expenses that reduce taxable income. These findings indicate that formal corporate governance mechanisms alone may be insufficient to curtail tax avoidance. The low explanatory power of our model (0.7%) indicates that other factors significantly influence tax planning decisions. Our research contributes to understanding tax avoidance determinants in Indonesia's leading companies and highlights how asset structure affects tax behavior. For regulatory authorities, our findings suggest enhancing tax policies related to fixed asset depreciation and strengthening governance mechanisms beyond formal requirements. Tax authorities should scrutinize depreciation practices in capital-intensive industries and develop more sophisticated audit procedures targeting book-tax differences. Future research should incorporate additional variables such as political connections, executive characteristics, and business complexity, employ alternative tax avoidance measures, and explore moderating relationships to develop a more comprehensive understanding of tax avoidance drivers in emerging markets.